The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1526-4637.2008.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Point Injections for Chronic Non-Malignant Musculoskeletal Pain: A Systematic Review

Abstract: The efficacy of TPI is no more certain than it was a decade ago as, overall, there is no clear evidence of either benefit or ineffectiveness. The only advantage of injecting anesthetic into trigger points may be to reduce the pain of the needling process, which may not be an insignificant benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 58 publications
2
82
0
1
Order By: Relevance
“…35,46 TrP dry needling (TrPDN) is one proposed treatment method 15 that has been shown to reduce TrP-associated pain. 38,43 A recent meta-analysis concluded that there is grade A (high-level) evidence to support the use of TrPDN in patients with upperquarter myofascial pain, particularly chronic neck and shoulder pain. 27 However, additional well-designed studies are needed to further examine treatment effectiveness.…”
Section: T T Conclusionmentioning
confidence: 99%
“…35,46 TrP dry needling (TrPDN) is one proposed treatment method 15 that has been shown to reduce TrP-associated pain. 38,43 A recent meta-analysis concluded that there is grade A (high-level) evidence to support the use of TrPDN in patients with upperquarter myofascial pain, particularly chronic neck and shoulder pain. 27 However, additional well-designed studies are needed to further examine treatment effectiveness.…”
Section: T T Conclusionmentioning
confidence: 99%
“…13 Ischemic compression has the advantage of being a noninvasive and inexpensive therapy that should not increase anxiety levels of patients. 22 However, although it is a relatively simple technique, if it is performed improperly-for example, without adequate analgesia-ischemic compression can exacerbate the patient's pain and perpetuate the pain cycle.…”
Section: Mitidieri Et Almentioning
confidence: 99%
“…3 Treatment of AMPS requires a multidisciplinary approach, with the goals of interrupting the pain cycle, abolishing the myofascial trigger points, and restoring muscle flexibility by eliminating predisposing factors and perpetuation of the pain. 18 In addition to symptomatic treatment with analgesics, muscle relaxants, antidepressants, and nonsteroidal anti-inflammatory drugs (NSAIDs), 13 specific treatments, such as local anesthetic blockade in trigger points, [19][20][21][22] ischemic compression, 13,23,24 electrotherapy, 25 and Botulinum toxin [26][27][28][29][30] may be tried. Alternative or complementary therapies have also been used increasingly for musculoskeletal pain.…”
Section: Introduction Cmentioning
confidence: 99%
“…Nevertheless, a common finding of different studies in different pain syndromes is an average improvement, irrespective of the technique or the injectate. 31,38 Because of the lack of high-quality randomized controlled trials, it is unclear whether the improvement is the result of a specific effect of the trigger point treatments or a placebo effect and regression to the mean. Because trigger point treatments are associated with minimal risks, I pragmatically propose to offer them to patients who display trigger points, in the hope of facilitating spontaneous recovery or rehabilitation strategies to reduce pain and improve function.…”
Section: Therapeutic Proceduresmentioning
confidence: 99%